Culture and Healthy Eating: The Role of Independence and Interdependence in the United States and Japan. (October 2016) - Levine, Cynthia S.; Miyamoto, Yuri; Markus, Hazel Rose; Rigotti, Attilio; Boylan, Jennifer Morozink; Park, Jiyoung; Kitayama, Shinobu; Karasawa, Mayumi; Kawakami, Norito; Coe, Christopher L.; Love, Gayle D.; Ryff, Carol D.
Healthy eating is important for physical health. Using large probability samples of middle-aged adults in the United States and Japan, we show that fitting with the culturally normative way of being predicts healthy eating. In the United States, a culture that prioritizes and emphasizes independence, being independent predicts eating a healthy diet (an index of fish, protein, fruit, vegetables, reverse-coded sugared beverages, and reverse-coded high fat meat consumption; Study 1) and not using nonmeat food as a way to cope with stress (Study 2a). In Japan, a culture that prioritizes and emphasizes interdependence, being interdependent predicts eating a healthy diet (Studies 1 and 2b). Furthermore, reflecting the types of agency that are prevalent in each context, these relationships are mediated by autonomy in the United States and positive relations with others in Japan. These findings highlight the importance of understanding cultural differences in shaping healthy behavior and have implications for designing health-promoting interventions.